Systemic liquidity shortages and interbank network structures - Lee, Seung Hwan (Journal of Financial Stability, 2013)
This paper aims to shed light on the systemic nature of liquidity risk and to propose a method for calculating systemic liquidity shortages. Our method incorporates not only direct liquidity shortages but also indirect liquidity shortages due to the knock-on effects through interbank linkages. We perform a simulation with a simple banking system model and find that a deficit bank can mitigate a liquidity shortage by holding more claims on a surplus bank. Meanwhile, a greater imbalance in liquidity positions across banks tends to aggravate the liquidity shortage of a deficit bank. According to comparative analysis between different types of network structures, a core-periphery network with a deficit money center bank gives rise to the highest level of systemic liquidity shortage, and a banking system becomes more vulnerable to liquidity shocks as its interbank network becomes more ill-matched.